A comparative review on greenery ecosystems and their impacts on sustainability of building environment - Al-Kayiem, H.H. (MDPI, 2020)
Greenery systems are sustainable ecosystems for buildings. Many studies on greenery systems, such as green roofs and green walls, have demonstrated that greenery systems support energy saving and improve thermal conditions in the building sector. This paper summarizes, discusses, and compares greenery systems and their contributions to the reduction of the urban heat index, the reduction of internal and external buildingsâ wall temperatures, and the reduction of the energy consumption of buildings. The fundamental mechanisms of greenery systems, which are thermal insulation, evapotranspiration, and shading effect, are also discussed. The benefits of greenery systems include the improvement of stormwater management, the improvement of air quality, the reduction of sound pollution, the reduction of carbon dioxide, and the improvement of aesthetic building value. The summarized materials on the greenery systems in the article will be a point of references for the researchers, planners, and developers of urban and rural areas, as well as the individualâs interest for future urban and rural plans. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.